Dynamic Behavior of Viscous Droplets Impact on a Flexible Mesh Surface - Gu, Hao (Langmuir : the ACS journal of surfaces and colloids, 2024)
The dynamic behavior of a viscous droplet impacting a flexible mesh surface with a fixed end is studied by high-speed photography in this work. Our experimental results reveal that surface vibration occurs when the viscous droplet impacts the flexible mesh surface. Simultaneously, the droplet spreads on the upper surface and penetrates into the mesh surface, resulting in a decrease in the spreading diameter on the upper surface. On the lower surface, the droplet elongates and forms multiple ligaments. Notably, different dynamic behaviors are observed when the droplet impacts surfaces with varying Weber (We) numbers due to viscous dissipation and surface vibration. However, as the impact position deviates from the fixed end, the surface vibrational amplitude increases, leading to a decreased diffusion range of the droplet on the lower surface. In addition, the vibration amplitude significantly enhances with increase of the We number. The vibration induces stretching and eventual rupture of the cardinal ligament under specific conditions. The first breaking time of the cardinal ligament delays with the decrease of the We number. As the impact position moves away from the fixed end, this situation is enhanced. Especially, when the stretching direction of the ligament is inconsistent with the vibration direction of the surface, the vibration has a great influence on the stretching behavior of the cardinal ligament